EXPLORING CREATIVE THINKING SKILL - Wulandari, Hilaria Yesieka Ayu; Ekawati, Rooselyna; Shodikin, Ali (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2024)
This study aims to describe students' abilities with visual-spatial and logical-mathematical intelligence in solving contextual mathematical problems. This qualitative research involved two eighth-grade students from a junior high school, each with a background in logical-mathematical and visual-spatial intelligence. The task consisted of two questions that asked students to create two park designs and two alternative payment methods for the